DDQ-Mediated Cross-Dehydrogenative-Coupling Reaction of Secondary Amines with Dialkyl Phosphonates - Cheng, Ming-Xing; Lei, Jing-Wei; Xie, Cai-Xia (Synlett, 2019)
This work reports a DDQ-mediated cross-dehydrogenative-coupling reaction of secondary amines with dialkyl phosphonates under mild conditions. This reaction proceeds efficiently without involving visible light or transition-metal catalysis. This new approach provides efficient access to biologically important α-aminophosphonates.
Keywords: DDQ; cross-dehydrogenative-coupling; phosphonylation; allylic amines; dialkyl phosphonates; aminophosphonates